Burst Pressure Assessment of Corroded Steel Pipeline Using DNV-RP-F101 and Finite Element Method with Circumferential Defect Interaction Study - Yoyok Setyo Hadiwidodo; Asta Razqi Damarjati; Herman Pratikno (International Journal of Offshore and Coastal Engineering, 2026)
Metal loss corrosion is one of the primary degradation mechanisms in steel pipelines in the oil and gas industry. Wall thickness reduction due to corrosion increases hoop stress and reduces the maximum pressure capacity of the pipeline, potentially leading to bursting failure. This study aims to analyze the bursting pressure of corroded steel pipelines using two approaches: the analytical method based on DNV-RP-F101 and the numerical method using the Finite Element Method (FEM) through ANSYS software. The parameters investigated include the defect depth ratio (d/t) and the circumferential spacing between defects. A three-dimensional numerical model was developed considering elastic-plastic material behavior. The results indicate that an increase in defect depth ratio has a dominant effect in reducing bursting pressure, while closer defect spacing intensifies stress interaction and accelerates local plastification. A comparison between DNV-RP-F101 and FEM shows deviations within acceptable engineering tolerance; however, FEM predicts lower failure pressure as it captures stress concentration and plastic distribution in greater detail.